NASIONALISME SEBAGAI AJARAN SPIRITUAL PENGHAYAT - Sari, Dian Kurnia (IAIN Tulungagung, 2018)
Nationalism is a sacred spiritual teaching for the adherents of local beliefs, especially Kaweruh Jowo Dipo. This sacred teaching carries the spirit of protecting the archipelago. The assumption of taking care the archipelago is a part of preserving the heritage for the harmony of a nation?s life. Religious groups such as Kaweruh Jowo Dipo plays a vital role in affirming and taking care of this sacred teaching. This research focuses on one point: how the teachings of nationalism become spiritual teachings for the Kaweruh Jowo Dipo. This research uses descriptive qualitative research using specific methods, such as ethnographic-based Native Point of View. The results of this study indicate that the teachings of nationalism are absorbed from the humanist teachings of ancestors. This teaching is packaged through songs and practices of the adherents of Kaweruh Jowo Dipo. The doctrine stated that nationalism is one of the mantras towards humanist behaviors. Keywords: Nationalism, Adherents of Jowo Dipo, Spiritual teachings Nasionalisme merupakan ajaran sipritual yang sakral bagi pelaku Penghayat, khususnya Kaweruh Jowo Dipo. Ajaran sakral ini mengusung semangat menjaga Nusantara. Asumsi penjagaan terhadap Nusantara merupakan bagian dari penjagaan warisan leluhur untuk keharmonisan hidup berbangsa. Kelompok agama seperti Kaweruh Jowo Dipo mempunyai andil dalam meneguhkan dan merawat ajaran sakral ini. Penelitian ini memfokuskan pada satu titik, bagaimana ajaran nasionalisme ini menjadi ajaran spiritual bagi kelompok Penghayat Kaweruh Jowo Dipo. Penelitian ini menggunakan jenis penelitian kualitatif-deskriptif. Dengan metode spesifik, etnografi-basis Native Point of View. Adapun hasil dari penelitian ini menunjukkan bahwa ajaran nasionalisme diserap dari ajaran nenek moyang yang berperikemanusiaan. Ajaran ini dikemas melalui kidung dan laku para penganut penghayat Kaweruh Jowo Dipo. Doktrinya, nasionalisme menjadi salah satu mantra menuju laku yang humanis. Kata kunci: Nasionalisme, Penghayat Jowo Dipo, Ajaran Spiritual